Formulasi Gel Sabun Wajah Ekstrak Etanol Daun Putihan (Chromolaena odorata L.) Sebagai Antijerawat - Monica Suryani; Manahan Situmorang; Steven Tandiono (Lembaga Pengembangan Kinerja Dosen, 2023)
Acne is a skin disease due to chronic inflammation with complex pathogenesis. The public has empirically used the white plant to treat wounds on the skin, it contains flavonoids, saponins, and tannins which can protect the skin from bacteria and can inhibit bacterial growth. This study aims to test the antibacterial activity against Propionibacterium acnes. The ethanol extract of Putihan leaves was obtained by maceration using 96% ethanol solvent, formulated and evaluated for facial soap gel preparations of ethanol extract of Putihan leaves with various extract concentrations of 0% (F0), 10% (F1), 13% (F2), and 15% (F3) which testing antibacterial activity against Propionibacterium acnes. The results showed that the antibacterial activity of the facial soap gel preparation of ethanol extract of Putihan leaves with a concentration of 10% had an inhibition of 8.4 ± 0.20 mm, 13% had an inhibition of 9.5 ± 0.23 mm and 15% had an inhibition of 10.6 ± 0.64mm. Based on this description, the resulting gel preparation has antibacterial activity against Propionibacterium acne. The three formulas are included in the medium inhibition zone category, but the one with the broadest inhibition zone is at a concentration of 15%.